Diagnostics for SARS-CoV-2 infections - Kevadiya, Bhavesh D.; Machhi, Jatin; Herskovitz, Jonathan; Oleynikov, Maxim D.; Blomberg, Wilson R.; Bajwa, Neha; Soni, Dhruvkumar; Das, Srijanee; Hasan, Mahmudul; Patel, Milankumar; Senan, Ahmed M.; Gorantla, Santhi; et al. (Nature materials, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has spread to nearly every corner of the globe, causing societal instability. The resultant coronavirus disease 2019 (COVID-19) leads to fever, sore throat, cough, chest and muscle pain, dyspnoea, confusion, anosmia, ageusia and headache. These can progress to life-threatening respiratory insufficiency, also affecting the heart, kidney, liver and nervous systems. The diagnosis of SARS-CoV-2 infection is often confused with that of influenza and seasonal upper respiratory tract viral infections. Due to available treatment strategies and required containments, rapid diagnosis is mandated. This Review brings clarity to the rapidly growing body of available and in-development diagnostic tests, including nanomaterial-based tools. It serves as a resource guide for scientists, physicians, students and the public at large. This Review highlights the progress that has been made in the development of diagnostic tools for the detection of SARS-CoV-2 in the fight against COVID-19.